Negative electrode material, negative electrode sheet and secondary battery

By setting holes in the carbon matrix negative electrode material and depositing active substances to control the distribution of nitrogen elements, the structural failure and electrochemical performance attenuation caused by volume expansion of the silicon negative electrode material during the deintercalation process are solved, and the performance of secondary battery with high discharge specific capacity, first-time Coulomb efficiency and cycle stability are achieved.

CN119833614AActive Publication Date: 2025-04-15BTR NEW MATERIAL GRP CO LTD

Patent Information

Application Number
CN202510040372.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The volume expansion of silicon anode material during the deintercalation of lithium leads to structural damage and rapid attenuation of electrochemical properties.

Method used

A carbon matrix negative electrode material containing nitrogen is used. By providing pores in the carbon matrix and depositing active substances in the pores, the distribution of nitrogen elements is controlled to make it more concentrated inside the carbon matrix, thereby reducing the proportion of surfactant and reducing side reactions with the electrolyte.

Benefits of technology

The discharge specific capacity, first-time Coulomb efficiency and cycle stability of the negative electrode material are improved, the gas production behavior is reduced, and the conductive properties of the carbon matrix are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833614A_ABST
    Figure CN119833614A_ABST
Patent Text Reader

Abstract

The negative electrode material contains a nitrogen element and comprises a carbon substrate and an active substance, the carbon substrate is provided with holes, at least part of the active substance is arranged in the holes of the carbon substrate, a region which is 200 nm deep from the outer surface of the negative electrode material is defined as a first region, and the first region is defined as a second region. An area which is 1000 nm deep from the outer surface of the negative electrode material is a second area, the atomic percentage content of the nitrogen element in the first area is alpha, and the atomic percentage content of the nitrogen element in the second area is beta, alphalt; beta; the deposition parameter of the active substance is defined as gamma, and gamma is greater than or equal to 0.86. In the negative electrode material, relatively most of the active substances are distributed in the pores of the carbon matrix, so that the gas production behavior of the negative electrode material is reduced, and the conductive performance of the carbon matrix is favorably exerted, so that the secondary battery applying the negative electrode material has relatively high specific discharge capacity, initial coulombic efficiency and relatively good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage, and in particular to a negative electrode material, a negative electrode sheet and a secondary battery. Background Art

[0002] With the rapid development and widespread application of electric vehicles, the market has put forward higher requirements for the energy density and cycle life of secondary batteries (such as lithium-ion batteries). The energy density of lithium-ion batteries mainly depends on the choice of electrode materials. The traditional mainstream negative electrode materials mainly include graphite, but the specific capacity of graphite negative electrode is close to the theoretical upper limit and it is almost difficult to increase it further. The theoretical capacity of silicon is about 4200mAh / g. It has the advantages of high capacity, wide sources, environmental friendliness, and moderate lithium insertion potential. It is generally considered to be one of the next generation of high specific energy candidate lithium-ion battery negative electrode materials.

[0003] However, the volume of silicon expands significantly during the process of lithium insertion and extraction, which can easily cause the silicon particles to break and pulverize, thereby destroying the electrode structure or causing problems such as repeated growth of the solid electrolyte interface (SEI) film, resulting in rapid decay of the electrochemical performance of the silicon negative electrode. Summary of the invention

[0004] In view of this, the present application provides a negative electrode material to solve at least one of the above problems.

[0005] To achieve the above-mentioned purpose, the present application provides a negative electrode material, the negative electrode material contains nitrogen, the negative electrode material includes a carbon matrix and an active substance, the carbon matrix is ​​provided with pores, at least part of the active substance is provided in the pores of the carbon matrix, a region with a depth of 200nm from the outer surface of the negative electrode material is defined as a first region, a region with a depth of 1000nm from the outer surface of the negative electrode material is defined as a second region, the atomic percentage content of the nitrogen element located in the first region is α, the atomic percentage content of the nitrogen element located in the second region is β, α<β; the deposition parameter of the active substance is defined as γ, γ≥0.86; wherein, ρ is the density of the active material; m1 is the mass of the negative electrode material, based on m1, the mass percentage of the active material is a1, and the specific pore volume of the negative electrode material is p1; m2 is the mass of the negative electrode material after removing the active material, based on m2, the mass percentage of the active material is a2, and the specific pore volume of the negative electrode material after removing the active material is p2.

[0006] In some possible implementations, 0.5≤α<β≤10.

[0007] In some possible implementations, the negative electrode material includes a core and a coating layer provided on at least a portion of the surface of the core, the core includes a carbon matrix and an active substance, and the material of the coating layer includes one or more of carbon material, metal oxide, amorphous silicon, conductive polymer, fluoride, phosphate and nitride.

[0008] In some possible implementations, the thickness of the coating layer is 5 nm to 200 nm.

[0009] In some possible implementations, the mass proportion of the coating layer in the negative electrode material is less than or equal to 10%.

[0010] In some possible implementations, the specific surface area of ​​the carbon matrix is ​​800 m 2 / g to 3000m 2 / g.

[0011] In some possible implementations, the total pore volume of the carbon matrix is ​​0.5 cm 3 / g to 2.0cm 3 / g.

[0012] In some possible implementations, the porosity of the carbon matrix is ​​40% to 80%.

[0013] In some possible implementations, the carbon matrix includes one or more of hard carbon, soft carbon, natural graphite, artificial graphite, carbon nanotubes, carbon fibers, and graphene.

[0014] In some possible implementations, the active material includes one or more of Li, Na, K, Sn, Ge, Si, Fe, Mg, SiO, Ti, Zn, Al, P, and Cu.

[0015] In some possible implementations, the active material includes a silicon material, and the silicon material includes one or more of amorphous silicon, crystalline silicon, and a composite of crystalline silicon and amorphous silicon.

[0016] In some possible implementations, the silicon material includes one or more of silicon particles, silicon oxides, and silicon alloys.

[0017] In some possible implementations, the silicon material includes silicon particles and a silicon oxide layer located on the surface of the silicon particles, and the silicon oxide layer includes silicon oxide.

[0018] In some possible implementations, the average particle size of the silicon material is 0.1 nm to 500 nm.

[0019] In some possible implementations, the active material includes a silicon material, the coating layer includes a carbon material, and based on the mass of the negative electrode material, the mass proportion of carbon element in the negative electrode material is 40% to 60%.

[0020] In some possible implementations, based on the mass of the negative electrode material, the mass proportion of silicon element in the negative electrode material is 30% to 65%.

[0021] In some possible implementations, the specific surface area of ​​the negative electrode material is 0.5 m 2 / g to 10m 2 / g.

[0022] In some possible implementations, the powder conductivity of the negative electrode material is 0.5 S / cm to 3 S / cm.

[0023] In some possible implementations, the 24-hour gas production value of the negative electrode material is less than or equal to 4cc / kg.

[0024] In some possible implementations, the median particle size of the negative electrode material is 5 μm to 20 μm.

[0025] In some possible implementations, the particle size distribution of the negative electrode material is (D90-D10) / D50 is 0.9 to 5.

[0026] In some possible implementations, the compaction density of the negative electrode material at a pressure of 1 T is 0.8 g / cm 3 Up to 1.3g / cm 3 .

[0027] In some possible implementations, the tap density of the negative electrode material after 3000 vibrations is 0.5 g / cm 3 Up to 1.5g / cm 3 .

[0028] The present application also provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer comprises the above-mentioned negative electrode material.

[0029] The present application also provides a secondary battery, comprising the above-mentioned negative electrode sheet.

[0030] In the present application, the second region is closer to the interior of the carbon matrix than the first region. By setting the relationship between α and β, more nitrogen elements are distributed inside the carbon matrix rather than on the surface. Such distribution is conducive to promoting the deposition of more active substances in the pores of the carbon matrix, so that the active substance deposition parameter γ is greater than or equal to 0.86, thereby relatively reducing the proportion of active substances distributed on the surface of the carbon matrix, thereby reducing the side reaction between the surface of the negative electrode material and the electrolyte, reducing the gas production behavior of the negative electrode material, and is conducive to the conductivity of the carbon matrix. Therefore, the secondary battery using this negative electrode material can have a higher discharge specific capacity, first coulomb efficiency and better cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of the structure of a secondary battery provided in one embodiment of the present application during charging.

[0032] Figure 2 A schematic diagram of the structure of a secondary battery provided in one embodiment of the present application during discharge.

[0033] Figure 3 This is a morphology test image of the negative electrode material provided in Example 1 of the present application.

[0034] Figure 4 This is the XRD test spectrum of the negative electrode material provided in Example 1 of the present application.

[0035] Main component symbols

[0036] Electrode assembly 100

[0037] Positive electrode 101

[0038] Negative electrode 102

[0039] Isolation film 103. DETAILED DESCRIPTION

[0040] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0041] In order to solve the problem caused by the expansion of silicon particles in the silicon negative electrode, the innovation of silicon-carbon negative electrode materials has emerged in the field of lithium-ion batteries. It combines the high specific capacity of silicon and the stability of carbon, aiming to improve the energy density and cycle life of the battery. In order to further play the advantages of silicon-carbon negative electrode materials and increase the capacity of silicon-carbon negative electrodes, this application seeks a method to increase the loading amount of silicon from the perspective of structural design. This application finds that in the process of silicon and carbon compounding, a large amount of silicon is easily exposed on the surface of the carbon material, causing the silicon-carbon negative electrode material to produce a huge volume effect during the lithium extraction process, and affecting the conductivity of the entire negative electrode material; the exposed silicon particles may also have obvious gas production behavior in the aqueous slurry or electrolyte system, which brings safety hazards, and is also not conducive to the capacity of the silicon-carbon negative electrode material, resulting in a decrease in the first coulombic efficiency.

[0042] Based on this, the present application improves the preparation method of silicon-carbon negative electrode materials. On the basis of the same silicon deposition amount, the content of silicon exposed on the surface of the carbon material is reduced, thereby achieving the purpose of improving the capacity of the silicon-carbon negative electrode material, the first coulombic efficiency and improving the cycle stability.

[0043] Based on this, an embodiment of the present application provides a secondary battery, comprising a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.

[0044] The outer shell can be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), for example, a soft-pack battery. In other embodiments, it can also be a steel shell battery, an aluminum shell battery, etc.

[0045] See also Figure 1 and Figure 2 The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103. The separator 103 is disposed between the positive electrode sheet 101 and the negative electrode sheet 102. When an electrolyte (not shown) is provided, when charging, please refer to Figure 1 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material (such as the lithiated intercalation compound) of the positive electrode sheet 101, pass through the separator 103 through the electrolyte, reach the negative electrode sheet 102 and insert into the lattice of the negative electrode material. Figure 2 , active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode sheet 102, pass through the isolation membrane 103 through the electrolyte, reach the positive electrode sheet 101 and are embedded in the lattice of the positive electrode material (such as the lithiated intercalation compound), and generate electrons that reach the positive electrode sheet 101 from the negative electrode sheet 102 through the external circuit. The reverse movement of the electrons forms an electric current, which can be used by electrical appliances.

[0046] In some embodiments, the electrode assembly 100 may be a laminated structure, which is formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.

[0047] Positive electrode

[0048] The positive electrode sheet 101 includes a positive electrode current collector and a positive electrode material active layer provided on at least one surface of the positive electrode current collector. The positive electrode current collector may be made of aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode material active layer includes a positive electrode active material, and the positive electrode active material includes a compound that can reversibly embed and deintercalate lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5O4) or at least one of lithium iron phosphate (LiFePO4).

[0049] The positive electrode material active layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode material active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.

[0050] The positive electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0051] Negative plate

[0052] The negative electrode sheet 102 includes a negative electrode current collector and a negative electrode material active layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.

[0053] The negative electrode material active layer includes a negative electrode material, the negative electrode material contains nitrogen, the negative electrode material includes a carbon matrix and an active substance, the carbon matrix is ​​provided with pores, at least part of the active substance is provided in the pores of the carbon matrix, a region at a depth of 200 nm from the outer surface of the negative electrode material is defined as a first region, a region at a depth of 1000 nm from the outer surface of the negative electrode material is defined as a second region, the atomic percentage of the nitrogen element located in the first region is α, the atomic percentage of the nitrogen element located in the second region is β, α<β.

[0054] Define the deposition parameter of active material as γ, γ≥0.86; wherein, ρ is the density of the active material; m1 is the mass of the negative electrode material, based on m1, the mass percentage of the active material is a1, and the specific pore volume of the negative electrode material is p1; m2 is the mass of the negative electrode material after removing the active material, based on m2, the mass percentage of the active material is a2, and the specific pore volume of the negative electrode material after removing the active material is p2.

[0055] The present application has found that when the negative electrode material contains nitrogen distribution, nitrogen atoms will cause changes in the local surface chemical activity of the carbon matrix, which may affect the contact between the carbon matrix and other substances. The present application further finds that when the negative electrode material is divided into the above-mentioned first region and the second region, the second region is closer to the inside of the carbon matrix than the first region. By setting the relationship between α and β, more nitrogen elements are distributed inside the carbon matrix rather than on the surface. Taking the vapor-deposited active material as an example, such a distribution is conducive to promoting more gas-phase active material sources (such as gas-phase silane) to crack and deposit in the pores of the carbon matrix, thereby promoting more active materials to be deposited in the pores of the carbon matrix, so that the active material deposition parameter γ is greater than or equal to 0.86, thereby being able to relatively reduce the proportion of active materials distributed on the surface of the carbon matrix, thereby reducing the side reaction between the surface of the negative electrode material and the electrolyte, reducing the gas production behavior of the negative electrode material, and being conducive to the conductivity of the carbon matrix. The secondary battery using the negative electrode material can have a higher discharge specific capacity, first coulomb efficiency and better cycle stability.

[0056] It can be understood that when α is greater than β, nitrogen atoms are distributed in the more superficial areas of the carbon matrix, and the content of nitrogen atoms distributed inside the carbon matrix is ​​relatively small. The role of nitrogen atoms in enhancing the adsorption capacity of the carbon matrix pores for active substances is relatively weak, and the active substances tend to be deposited on the surface of the carbon matrix, resulting in an increase in side reactions between the negative electrode material and water or electrolyte, and an intensification of the gas production behavior of the negative electrode material, which is not conducive to the use of the capacity of the secondary battery, resulting in a decrease in the first coulombic efficiency and cycle stability.

[0057] In the above calculation formula of γ, the polynomial m2×p2-m1×p1 represents the difference between the pore volume of the negative electrode material after the active material is removed and the pore volume of the provided negative electrode material, which is used to characterize the volume of the active material in the carbon matrix pores in the provided negative electrode material; the polynomial m1×a1-m2×a2 represents the difference between the mass of the active material in the provided negative electrode material and the mass of the active material in the negative electrode material after the active material is removed, which is used to characterize the total mass of the active material removed by the acid solution in the provided negative electrode material (including all active materials in the carbon matrix pores and other positions of the carbon matrix), and the ratio of the polynomial m1×a1-m2×a2 to the density ρ of the active material corresponds to the total volume of the active material in the provided negative electrode material. Therefore, the calculation formula of γ is used to characterize the proportion of the active material in the carbon matrix pores in the negative electrode material to the total active material.

[0058] In some embodiments, removing active substances from the negative electrode material comprises: mixing the negative electrode material with an acid solution. The negative electrode material is mixed with an acid solution of sufficient concentration, stirred sufficiently, and the negative electrode material is etched with the acid solution, so that the active substances in the pores of the carbon matrix of the negative electrode material and on the surface of the carbon matrix can be removed to a certain extent, and the active substances are removed after the etched negative electrode material is cleaned and dried.

[0059] In some embodiments, the acid solution includes one or more of hydrochloric acid, nitric acid, and hydrofluoric acid.

[0060] In some embodiments, taking silicon material as an active material in the negative electrode material as an example, the above-mentioned "negative electrode material removal of active material" includes: using 70% hydrochloric acid and 50% hydrofluoric acid in a volume ratio of 2:1 to form an acid solution, placing the negative electrode material in the acid solution and stirring for at least 10 hours, and then washing and drying the negative electrode material. In the calculation formula of γ, ρ can take a value of 2.34, and the deposition parameter γ of the silicon material is calculated, which can further characterize the proportion of silicon material deposited in the pores of the carbon matrix.

[0061] In the related art, taking silicon material as an active substance as an example, when the content of silicon material reaches a certain level, part of the silicon material will begin to adhere to the surface of porous carbon, thereby significantly increasing the specific surface area of ​​the negative electrode material, resulting in increased contact between the negative electrode material and the electrolyte and increased side reactions during the charge and discharge process, making it more difficult to maintain a stable SEI film; and, the silicon particles attached to the surface of the carbon matrix are easily hydrolyzed during slurry preparation and battery use, producing a large amount of gas, thereby resulting in decreased slurry stability and potential safety hazards to the battery; in addition, when the content of silicon material in the negative electrode material is constant, a higher content of silicon material on the surface of the carbon matrix means that the content of silicon material filled in the carbon matrix is ​​less, so that excess pores may be generated inside the particles, resulting in the problem of decreased strength of the negative electrode material particles. The present application measures the pore volume change and mass change of the negative electrode material before and after the removal of the active material, and then characterizes the proportion of the active material in the carbon matrix pores in the negative electrode material, that is, the deposition parameter γ. In the present application, when the active material deposition parameter γ is greater than or equal to 0.86, it means that most of the active material is distributed in the pores of the carbon matrix, which can reduce the side reaction between the negative electrode material and the electrolyte during the charge and discharge process, improve the cycle performance of the battery, and reduce the hydrolysis of the active material during pulping and battery use, that is, reduce the generation of gas, and improve the safety performance of the battery. In addition, when the content of silicon material in the negative electrode material is constant, the increase in the content of silicon material in the carbon matrix pores can also increase the particle strength of the negative electrode material. In other embodiments, when the deposition parameter γ is less than 0.86, the specific pore volume, specific surface area, micropore (pores with a pore size of less than or equal to 2nm) and gas production of the obtained negative electrode material increase significantly, which is not conducive to obtaining good electrochemical performance. This can also explain that the present application has important practical application value in obtaining negative electrode materials with relatively more active substances arranged in the carbon matrix pores by setting the deposition parameter γ to be greater than or equal to 0.86.

[0062] The negative electrode material that meets the above-mentioned α, β and γ requirements has an excellent filling effect of active substances. A relatively large part of the active substances are distributed in the pores of the carbon matrix, which reduces the gas production behavior of the negative electrode material and is beneficial to the conductivity of the carbon matrix. Therefore, the secondary battery using the negative electrode material has a higher discharge specific capacity, first coulomb efficiency and better cycle stability.

[0063] In some embodiments, 0.5≤α<β≤10. For example, α can be independently exemplified as 0.5, 1.0, 1.5, 1.8, 1.9, 2.2, 2.7, 2.9, 3, 4, 5, 6, 7, 8, 9, or any value within the range formed by any two of the above values; or β can be independently exemplified as 1, 2, 3, 4, 4.7, 4.8, 5.2, 5.6, 7.8, 8.9, 9.5, 9.8, 10, or any value within the range formed by any two of the above values; or α and β can be 1.5 and 5.6, 2.1 and 10, 1.0 and 4.8, 1.9 and 8.9, 0.5 and 4.7, 2.9 and 9.8, 2.7 and 9.5, 2.2 and 7.8, 1.8 and 5.2, or any other numerical combination that satisfies the above relationship. It can be understood that controlling the size of α and β can regulate the content of nitrogen atoms in the carbon matrix. When α and β satisfy the above relationship and range, it is beneficial to form sufficient nitrogen doping in the carbon matrix, which is beneficial to better play the role of nitrogen atoms in enhancing the adsorption capacity of the carbon matrix pores for active substances, promote relatively more active substances to be distributed in the pores of the carbon matrix, further reduce the side reactions between the surface of the negative electrode material and the electrolyte, further limit the gas production behavior of the negative electrode material, improve the capacity of the secondary battery, and improve the first coulombic efficiency and cycle stability.

[0064] In some embodiments, the negative electrode material includes a core and a coating layer disposed on at least a portion of the surface of the core, the core includes a carbon matrix and an active substance, and the material of the coating layer includes one or more of a carbon material, a metal oxide, amorphous silicon, a conductive polymer, a fluoride, a phosphate, and a nitride. The coating layer can reduce the solubility of the core portion of the negative electrode material in the electrolyte, thereby reducing the amount of gas produced by the reaction of the dissolved active substance (such as silicon material) with the electrolyte. The carbon material may include one or more of graphene, soft carbon, and hard carbon. The carbon coating layer located on the outer layer of the negative electrode material has good electrical conductivity and can improve the electrical conductivity of the negative electrode material.

[0065] In some embodiments, the coating layer may be a single-layer coating layer formed of the above-mentioned single material, or a coating layer formed by a combination of the above-mentioned multiple materials, or a multi-layer coating layer formed of a single material, or a multi-layer coating layer formed of multiple materials, etc. The layer structure of the coating layer can be selected according to actual needs. When the coating layer is a multi-layer coating structure, the density is higher.

[0066] In some embodiments, the coating layer has a thickness of 5 nm to 200 nm. For example, the coating layer may have a thickness of 5 nm, 10 nm, 20 nm, 30 nm, 60 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, or any value within the range formed by any two of the above values. Controlling the coating layer thickness within the above range can ensure the strength of the coating layer without affecting the energy density, which is beneficial for the negative electrode material to maintain the stability of the particle structure during the cycle, reduce the exposed active material on the surface of the negative electrode material, and reduce the risk of generating a large amount of SEI during the charge and discharge process due to the exposed active material, while maintaining a good interface resistance of the negative electrode material, and improving the specific capacity and electrochemical performance of the negative electrode material.

[0067] In some embodiments, the mass proportion of the coating layer in the negative electrode material is less than or equal to 10%. For example, the mass proportion of the coating layer can be 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, or any value within the range formed by any two of the above values. The mass proportion of the coating layer in the negative electrode material is within the above range, which can make the electrode active ions have sufficient embedding amount, thereby making the battery have a higher charge and discharge capacity, and is conducive to reducing the risk of decreased conductivity.

[0068] In some embodiments, the specific surface area of ​​the carbon matrix is ​​800 m 2 / g to 3000m 2 / g. For example, the specific surface area of ​​the carbon matrix can be 800m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g、1600m 2 / g、1800m 2 / g, 2000m 2 / g, 2300m 2 / g、2500m 2 / g、2800m 2 / g、3000m 2 / g or any value within the range formed by any two of the above values. Controlling the specific surface area of ​​the carbon matrix within the above range is conducive to the uniform dispersion and stable attachment of the active material on the carbon matrix, thereby helping to reduce the risk of the active material falling off from the carbon matrix and improving the stability of the active material.

[0069] In some embodiments, the total pore volume of the carbon matrix is ​​0.5 cm 3 / g to 2.0cm 3 / g. For example, the total pore volume of the carbon matrix can be 0.5 cm 3 / g, 0.8cm3 / g, 1cm 3 / g, 1.2cm 3 / g, 1.5cm 3 / g, 1.8cm 3 / g, 2.0cm 3 / g or any value within the range formed by any two of the above values. The carbon matrix has abundant pores, which can accommodate active materials and reserve space for the volume expansion of the accommodated active materials, which is beneficial to improving the capacity and cycle stability of the battery prepared by the negative electrode material.

[0070] In some embodiments, the porosity of the carbon matrix is ​​40% to 80%. For example, the porosity of the carbon matrix can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value within the range formed by any two of the above values. Porosity refers to the percentage of the pore volume in the material to the total volume of the material in its natural state. Controlling the porosity of the carbon matrix within the above range is conducive to the good deposition of the active material, thereby reducing the volume expansion effect of the negative electrode material.

[0071] In some embodiments, the carbon matrix includes one or more of hard carbon, soft carbon, natural graphite, artificial graphite, carbon nanotubes, carbon fibers, and graphene. The carbon matrix can provide distribution sites for active substances and form a conductive network.

[0072] In some embodiments, the active material includes one or more of Li, Na, K, Sn, Ge, Si, Fe, Mg, SiO, Ti, Zn, Al, P and Cu. The carbon matrix is ​​combined with the above metal materials, and the metal materials can induce lithium (or sodium, potassium) to precipitate in the pores in the form of an alloy with it, thereby facilitating the increase of the lithium (or sodium, potassium) storage space of the carbon matrix. Combining the carbon matrix with phosphorus can improve the conductivity and help reduce the volume change of the negative electrode material during the discharge / charge process.

[0073] In some embodiments, the active material includes a silicon material, and the silicon material includes one or more of amorphous silicon, crystalline silicon, and a composite of crystalline silicon and amorphous silicon. When the active material includes a silicon material, the silicon material is used as a component of the negative electrode active material, which can increase the specific capacity of the negative electrode material, thereby increasing the energy density of the secondary battery. Preferably, the silicon material includes amorphous silicon. When the active material further includes amorphous silicon, amorphous silicon expands isotropically during the lithium insertion process, which can reduce the collapse of pores in the material, inhibit the rapid decay of the specific capacity of the negative electrode material, and is more conducive to improving the lithium insertion cycle performance of the negative electrode material.

[0074] In some embodiments, the silicon material includes one or more of silicon particles, silicon oxide, and silicon alloys. In some embodiments, the silicon material includes silicon particles and a silicon oxide layer located on the surface of the silicon particles, and the silicon oxide layer includes silicon oxide.

[0075] In some embodiments, the average particle size of the silicon material is 0.1nm to 500nm. For example, the average particle size of the silicon material can be 0.1nm, 0.5nm, 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 80nm, 100nm, 200nm, 300nm, 400nm, 450nm, 500nm or any value within the range formed by any two of the above values. For example, the silicon material can be silicon particles. By setting the average particle size of the silicon particles within the above range, the mechanical stress of the silicon particles when the volume expands can be reduced, so that the secondary battery maintains a good battery capacity, and reduces irreversible capacity loss, and can also shorten the electron and ion transmission path. At the same time, the size of the silicon particles is reduced, and the gap between adjacent silicon particles is increased, which can reserve space for the volume expansion of the silicon particles.

[0076] In some embodiments, the coating layer includes a carbon material, and the mass proportion of the carbon element of the negative electrode material is 40% to 60% based on the mass of the negative electrode material. For example, the mass proportion of the carbon element can be 40%, 43%, 45%, 50%, 53%, 55%, 58%, 60% or any value within the range composed of any two of the above values. It can be further preferably 40% to 55%. The carbon material is derived from the carbon matrix and the coating layer. The carbon material is composited with the silicon material, which can provide a conductive platform and buffer space for the silicon material, thereby improving the problems of structural instability and poor conductivity of the negative electrode material during the cycle.

[0077] In some embodiments, the active material includes a silicon material, and the mass proportion of the silicon element of the negative electrode material is 30% to 65% based on the mass of the negative electrode material. For example, the mass proportion of the silicon element of the negative electrode material can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or any value within the range formed by any two of the above values. It can be further preferably 45% to 60%. The main element composition of the silicon material is silicon element. The negative electrode material that combines the carbon matrix with the silicon material can effectively solve the expansion problem of the silicon material during the cycle, maintain the stability of the battery material, and improve the volume capacity of the material.

[0078] In some embodiments, the specific surface area of ​​the negative electrode material is 0.5 m 2 / g to 10m 2 / g. For example, the specific surface area of ​​the negative electrode material can be 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g or any value within the range formed by any two of the above values. When the specific surface area of ​​the negative electrode material is large, the SEI film on the surface of the negative electrode material will consume excessive lithium salts, and the volume effect is likely to cause electrical separation between particles, resulting in a decrease in the discharge capacity and coulomb efficiency of the battery. Therefore, the specific surface area of ​​the negative electrode material in this embodiment is small, which is beneficial to improving the capacity of the first discharge ratio and the first coulomb efficiency of the battery. Further, the specific surface area of ​​the negative electrode material can be preferably 0.5m 2 / g to 2.5m 2 / g. Further controlling the specific surface area of ​​the negative electrode material within the above range is beneficial to further improve the capacity of the first discharge ratio and the first coulombic efficiency of the battery.

[0079] In some embodiments, the powder conductivity of the negative electrode material is 0.5S / cm to 3S / cm. For example, the powder conductivity of the negative electrode material can be 0.5S / cm, 1S / cm, 1.5S / cm, 2S / cm, 2.5S / cm, 3S / cm, or any value within the range formed by any two of the above values. The powder conductivity of the negative electrode material reflects the electrical conductivity of the negative electrode material, and good electrical conductivity is conducive to the capacity of the battery. Further, the powder conductivity of the negative electrode material can preferably be 1.5S / cm to 3S / cm. The powder conductivity of the negative electrode material is further controlled within the above range, which is conducive to further improving the utilization of lithium in lithium-ion batteries.

[0080] In some embodiments, the 24-hour gas production value of the negative electrode material is less than or equal to 4cc / kg. For example, the 24-hour gas production value of the negative electrode material can be 0.5cc / kg, 0.6cc / kg, 0.8cc / kg, 0.9cc / kg, 1cc / kg, 1.1cc / kg, 1.2cc / kg, 1.3cc / kg, 2cc / kg, 2.5cc / kg, 3cc / kg, 4cc / kg or any value within the range formed by any two of the above values. The gas production value of the negative electrode material is low, which is beneficial to reduce the consumption of active substances and improve the cycle stability of the battery. Further, the 24-hour gas production value of the negative electrode material may preferably be less than 2.7cc / kg. The gas production value of the negative electrode material is further controlled within the above range, which is beneficial to further reduce the gas production behavior of the negative electrode material and improve the cycle stability.

[0081] In some embodiments, the median particle size D50 of the negative electrode material is 5 μm to 20 μm. For example, the median particle size D50 of the negative electrode material can be 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 17 μm, 20 μm, or any value within the range formed by any two of the above values. Controlling the median particle size of the negative electrode material within the above range is beneficial to improving the cycle performance of the negative electrode material.

[0082] In some embodiments, the particle size distribution (D90-D10) / D50 of the negative electrode material is 0.9 to 5. For example, the particle size distribution (D90-D10) / D50 of the negative electrode material can be 0.9, 1, 1.2, 1.5, 2, 2.6, 3, 3.5, 4, 4.3, 4.6, 4.8, 5, or any value within the range formed by any two of the above values. When the particle size distribution of the negative electrode material is within the above range, the large particles with larger particle sizes and the small particles with smaller particle sizes in the negative electrode material can cooperate with each other, and the small particles are filled in the pores between the large particles, which can increase the tap density of the negative electrode material.

[0083] Among them, the measured volume-based cumulative particle size distribution, D10 represents the particle size corresponding to when the cumulative particle size distribution percentage of the powder reaches 10%, D50 represents the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, and D90 represents the particle size corresponding to when the cumulative particle size distribution percentage reaches 90%.

[0084] In some embodiments, the compaction density of the negative electrode material at a pressure of 1 T is 0.8 g / cm 3 Up to 1.3g / cm 3 For example, the compacted density can be 0.8 g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 Or any value within the range formed by any two of the above values. Controlling the compaction density within the above range helps to reduce the diffusion path of lithium ions in the negative electrode material, thereby improving the rate performance of the battery.

[0085] In some embodiments, the tap density of the negative electrode material after 3000 vibrations is 0.5 g / cm 3 Up to 1.5g / cm 3 For example, the tap density can be 0.5 g / cm 3 , 0.7g / cm 3 , 0.9g / cm 3 , 1.1g / cm 3 , 1.3g / cm 3, 1.5g / cm 3 Or any value within the range formed by any two of the above values. Controlling the tap density within the above range is conducive to forming a suitable compactness of the internal structure of the negative electrode material, thereby improving the transmission of lithium ions and the conduction of electrons, increasing the battery energy density, extending the cycle life and improving safety performance.

[0086] The negative electrode material active layer also includes a binder to bind the negative electrode active material particles to facilitate the formation of a film layer, and can also improve the binding force between the negative electrode material active layer and the negative electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc.

[0087] The negative electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0088] Isolation film

[0089] The isolation membrane 103 includes a membrane layer with a porous structure, and its material includes but is not limited to at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, the isolation membrane 103 can be a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite membrane.

[0090] Electrolytes

[0091] The electrolyte has the function of conducting ions between the positive electrode sheet 101 and the negative electrode sheet 102. The state of the electrolyte can be one or more of a gel state, a solid state and a liquid state. In some embodiments, the electrolyte is an electrolyte. The electrolyte plays the role of conducting active ions between the positive electrode sheet 101 and the negative electrode sheet 102. In some embodiments, the electrolyte includes a lithium salt and an organic solvent. The lithium salt can be selected from but not limited to lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(SO2CF3)2, tris(trifluoromethylsulfonyl)methyl lithium (LiC(SO2CF3)3), lithium bis(oxalatoborate) (LiBOB) and lithium difluorophosphate (LiPO2F2) One or more. For example, the lithium salt is selected from LiPF6 because it can give high ionic conductivity and improve cycle characteristics. The organic solvent can be a carbonate compound, a carboxylate compound, an ether compound, Compounds, nitrile compounds, other organic solvents or combinations thereof. Examples of carbonate compounds include, but are not limited to, diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethylmethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.

[0092] Another embodiment of the present application further provides a method for preparing a negative electrode material, comprising:

[0093] The first step is to mix a carbon matrix, a zinc salt and an organic active agent, wherein the organic active agent includes one or more of polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP) and poloxamer (Pluronic F127), and heat them in a reducing gas atmosphere to reduce the zinc ions in the zinc salt and attach them to the carbon matrix to obtain a first precursor.

[0094] The organic active agent has amino and hydroxyl groups, for example, it can be a non-ionic active agent or anionic active agent, which can promote the reduction of zinc salt and promote the adhesion of elemental zinc on the surface and in the pores of the carbon matrix after reduction.

[0095] In some embodiments, the zinc salt includes one or more of zinc chloride, zinc nitrate, zinc acetate, and zinc sulfate.

[0096] In some embodiments, the reducing gas includes hydrogen. It is understandable that the reducing gas atmosphere may further include an inert gas, for example, the reducing gas atmosphere may be hydrogen, a mixture of hydrogen and helium, a mixture of hydrogen and nitrogen, and the like.

[0097] In some embodiments, the heating temperature is 600° C. to 800° C., and the heating time is 2 h to 6 h. For example, the heating temperature may be 600° C., 620° C., 650° C., 700° C., 750° C., 780° C., 800° C., or any value within the range formed by any two of the above values. The heating time may be 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, or any value within the range formed by any two of the above values.

[0098] Step 2: Mix and dissolve the first precursor with the acid solution to obtain a second precursor.

[0099] The acid solution can act on the metallic zinc attached to the surface of the carbon matrix to reduce the metallic zinc on the surface of the carbon matrix, thereby obtaining a carbon matrix precursor with metallic zinc attached to the pores, namely, a second precursor.

[0100] In some embodiments, the acid solution includes one or two of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.

[0101] In some embodiments, the concentration of the acid solution is 0.5mol / L to 2mol / L. For example, the concentration of the acid solution can be 0.5mol / L, 0.7mol / L, 1mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L, 2mol / L or any value within the range formed by any two of the above numerical values. In some embodiments, the dissolution time of the acid solution is 1h to 20h. For example, the dissolution time can be 1h, 3h, 5h, 8h, 10h, 12h, 15h, 17h, 19h, 20h or any value within the range formed by any two of the above numerical values. Controlling the concentration and dissolution time of the acid solution within the above range is conducive to the acid solution playing the role of removing the zinc element on the surface of the carbon matrix, and is also conducive to reducing the reaction of the acid solution with the zinc element in the carbon matrix pores.

[0102] The third step: reacting a mixture of ammonia and protective gas in a certain volume ratio with the second precursor under high temperature conditions, the concentration of ammonia is 1% to 50%, the reaction temperature is 400°C to 1000°C, the reaction time is 0.5h to 10h, and the reaction pressure is 1Pa to 100kPa to obtain a third precursor.

[0103] For example, the concentration of ammonia can be 1%, 5%, 10%, 15%, 20%, 30%, 40%, 45%, 50%, or any value within the range formed by any two of the above values. The reaction temperature can be 400°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, or any value within the range formed by any two of the above values. The reaction time can be 0.5h, 1h, 2h, 4h, 5h, 7h, 8h, 9h, 10h, or any value within the range formed by any two of the above values. The reaction pressure can be 1Pa, 50Pa, 500Pa, 1kPa, 10kPa, 20kPa, 40kPa, 60kPa, 80kPa, 100kPa, or any value within the range formed by any two of the above values.

[0104] Under negative pressure conditions, ammonia gas molecules are allowed to fully enter the pores of the carbon matrix, which is conducive to the doping of nitrogen atoms in the pore size of the carbon matrix. Nitrogen doping can increase the surface chemical activity of the carbon material to enhance the material's adsorption capacity for gas-phase silane molecules and improve the deposition effect. Controlling the concentration of ammonia in the above process within the above range is conducive to doping sufficient nitrogen atoms in the negative electrode material to exert the effect of the above nitrogen doping, and is conducive to forming a nitrogen atom distribution in the negative electrode material that conforms to a preset trend. Controlling the reaction temperature and reaction time in the above process within the above range is conducive to promoting the reaction of ammonia and the second precursor, thereby facilitating the doping of sufficient nitrogen atoms in the negative electrode material and forming a nitrogen atom distribution that conforms to a preset trend.

[0105] In some embodiments, the protective gas includes at least one of nitrogen, helium, neon, argon, and krypton.

[0106] Step 4: Mix the third precursor with the active material precursor, perform vapor deposition, and obtain the negative electrode material.

[0107] During the vapor deposition process, under the catalytic action of metallic elemental zinc, the active substances are deposited in the pores of the carbon matrix, so that the active substances in the prepared negative electrode material are mainly distributed in the pores of the carbon matrix, thereby reducing the reaction between the active substances attached to or dissolved from the surface of the negative electrode material and the electrolyte, effectively reducing the gas production value of the negative electrode material and increasing the powder conductivity of the negative electrode material, thereby improving the various performances of the battery prepared with the negative electrode material.

[0108] In some embodiments, when the active material is a silicon material, the active material precursor includes a silicon-containing gas, and the silicon-containing gas includes one or more of silane, disilane, trisilane, and tetrasilane.

[0109] In some embodiments, the concentration of the silicon-containing gas is 10% to 80%. For example, the concentration of the silicon-containing gas can be 10%, 15%, 20%, 30%, 50%, 70%, 80%, or any value within the range formed by any two of the above values. Further, the gas used to dilute the silicon-containing gas can be selected from one or both of an inert gas and hydrogen.

[0110] In some embodiments, the temperature of vapor deposition is 300°C to 800°C. For example, the temperature of vapor deposition can be 300°C, 400°C, 450°C, 500°C, 520°C, 550°C, 600°C, 700°C, 800°C or any value within the range formed by any two of the above values.

[0111] In some embodiments, the vapor deposition time is 0.5 h to 15 h. For example, the vapor deposition time can be 0.5 h, 1 h, 2 h, 5 h, 8 h, 10 h, 12 h, 15 h, or any value within the range formed by any two of the above values.

[0112] The process conditions of vapor deposition (such as deposition temperature and deposition time) will affect the deposition of silicon material in the pores of carbon material. Controlling the temperature and time of vapor deposition within the above range is beneficial to reducing the decomposition and deposition of the reaction gas before entering the pores of carbon material, and promoting the decomposition and deposition of the reaction gas after entering the pores.

[0113] In some embodiments, after the above-mentioned vapor deposition, the obtained product (i.e., the core) is further coated. The coating includes at least one of carbon coating, oxide coating, metal salt, polymer coating, etc. Further, it is preferred that a plurality of combined coating methods are used, such as carbon coating followed by oxide coating, or carbon coating followed by metal salt coating, etc.

[0114] In some embodiments, when the coating includes carbon coating, the material of the coating layer includes a carbon material, and the carbon material is derived from at least one of gaseous carbon, liquid carbon and solid carbon. The gaseous carbon includes at least one of methane, acetylene, ethylene, ethane, propane, propylene, gaseous benzene, gaseous toluene, gaseous xylene, gaseous ethanol, gaseous cyclohexane, gaseous methanol and gaseous acetone; the liquid carbon source includes at least one of n-hexane, toluene, benzene, xylene, methanol, ethanol, propanol, butanol, pentanol, acetone, butanone, 2-pentanone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, amyl acetate and glycerol. The solid carbon source includes at least one of polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose, citric acid, asphalt, furfural resin, epoxy resin and phenolic resin.

[0115] In some embodiments, the coating process includes mixing the coating material with the core and performing a heat treatment.

[0116] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0117] Embodiment 1:

[0118] A negative electrode material, the preparation method of which comprises:

[0119] S1, weigh 2kg zinc chloride and 400g Pluronic F127 and dissolve them in 20L water, then add 5kg activated carbon, stir for 24h, filter and dry, place in a rotary kiln, and calcine for 4h at 900°C in an argon atmosphere to obtain a first precursor.

[0120] S2, placing the first precursor in 20L 1mol / L dilute sulfuric acid and stirring for 4h, then washing the sample with pure water and drying it for later use, to obtain the second precursor.

[0121] S3, placing the second precursor in a reaction chamber, raising the temperature to 800° C. in a nitrogen atmosphere, maintaining the pressure in the chamber at 100 kPa, and then reacting the second precursor with a mixed gas consisting of 90% nitrogen and 10% ammonia for 2 hours to obtain a third precursor.

[0122] S4, adjusting the chamber temperature to 520°C, introducing silane and carrier gas into the chamber, the carrier gas being a mixture of nitrogen, argon and hydrogen, controlling the silane concentration to 15%, reacting for 10 hours, and obtaining the core material.

[0123] S5, adjust the chamber temperature to 700°C, introduce methane and carrier gas into the chamber, the carrier gas is a mixture of nitrogen, argon and hydrogen, and the methane concentration is controlled to be 15%, and maintain for 4 hours. Then turn off the methane gas, introduce nitrogen, and cool to room temperature.

[0124] S6, screening and grading the obtained samples to obtain the negative electrode material.

[0125] Embodiment 2:

[0126] The difference from Example 1 is that in S3, the composition of the mixed gas is adjusted to 80% nitrogen and 20% ammonia.

[0127] Embodiment 3:

[0128] The difference from Example 1 is that in S3, the reaction temperature is adjusted to 600°C.

[0129] Embodiment 4:

[0130] The difference from Example 1 is that in S3, the reaction temperature is adjusted to 1000°C.

[0131] Embodiment 5:

[0132] The difference from Example 1 is that in S3, the reaction time is adjusted to 0.5 h.

[0133] Embodiment 6:

[0134] The difference from Example 1 is that in S3, the reaction time is adjusted to 4 hours.

[0135] Embodiment 7:

[0136] The difference from Example 1 is that in S3, the composition of the mixed gas is adjusted to 80% nitrogen and 20% ammonia, the reaction temperature is adjusted to 700° C., the reaction pressure is adjusted to 50 kPa, and the reaction time is adjusted to 1 h.

[0137] Embodiment 8:

[0138] The difference from Example 1 is that in S3, the composition of the mixed gas is adjusted to 50% nitrogen and 50% ammonia, the reaction pressure is adjusted to 50 kPa, and the reaction time is adjusted to 0.5 h.

[0139] Embodiment 9:

[0140] The difference from Example 1 is that in S3, the composition of the mixed gas is adjusted to 95% nitrogen and 5% ammonia, the reaction temperature is adjusted to 700° C., and the reaction time is adjusted to 10 h.

[0141] Embodiment 10:

[0142] The difference from Example 1 is that S5 is not performed.

[0143] Embodiment 11:

[0144] The difference from Example 1 is that in S3, the treatment is carried out under normal pressure.

[0145] Embodiment 12:

[0146] The difference from Example 1 is that in S3, the composition of the mixed gas is adjusted to 99% nitrogen and 1% ammonia.

[0147] Embodiment 13:

[0148] The difference from Example 1 is that in S3, the reaction temperature is adjusted to 400°C.

[0149] Embodiment 14:

[0150] The difference from Example 1 is that in S3, the reaction time is adjusted to 10 min.

[0151] Comparative Example 1:

[0152] The difference from Example 1 is that S3 is not performed.

[0153] Comparative Example 2:

[0154] The difference from Example 1 is that in S3, the composition of the mixed gas is adjusted to 20% nitrogen and 80% ammonia.

[0155] Comparative Example 3:

[0156] The difference from Example 1 is that in S3, the reaction temperature is adjusted to 1800°C.

[0157] Comparative Example 4:

[0158] The difference from Example 1 is that in S3, the reaction time is adjusted to 20 hours.

[0159] Taking Example 1 as an example, a scanning electron microscope (Hitachi S4800) was used to test the negative electrode material obtained in Example 1. The voltage was 3 kV and the current was 10 μA. The image was focused and astigmatism was eliminated. Figure 3 The negative electrode material prepared in the embodiment of the present application is evenly distributed without obvious agglomeration, indicating that the preparation method of the present application can achieve uniform distribution of the coating on the graphite material.

[0160] Taking Example 1 as an example, the negative electrode material obtained in Example 1 was tested using an X-ray diffraction analyzer (Japan Rigaku Ultima lv.), with the X-ray source being copper (Cu) Kα line, the incident angle range being set to 10° to 90°, and the step length being set to 0.02°. Figure 4, a characteristic steamed bun peak appears at 2θ=28.4°, indicating that the silicon in the negative electrode material is mainly amorphous silicon.

[0161] The negative electrode materials obtained in the above examples 1-14 and comparative examples 1-4 were tested for the following physical properties and electrochemical properties:

[0162] 1. α and β test of negative electrode materials: The American Thermo Scientific K-Alpha equipment is used to perform X-ray photoelectron spectroscopy test on negative electrode materials. The whole test process is carried out in a glove box filled with argon gas. Each spectrum acquisition needs to test four fine spectra of C, O, Si, and N. The depth of each argon ion sputtering is 50nm. The specific test mode is: spectrum acquisition + etching 50nm, sputtering 4 times to measure the nitrogen atomic percentage at a depth of 200nm, sputtering 20 times to measure the nitrogen atomic percentage at a depth of 1000nm, and randomly sampling 10 times at the same depth for testing, and taking the average value to obtain α and β.

[0163] 2. Test of deposition parameter γ of silicon material in negative electrode material: Take negative electrode material with mass m1, use American Micrometer ASAP2460 micropore specific surface area and pore size analyzer to measure specific pore volume p1, use Nanyang Xinyu SA2-9-17TP box atmosphere furnace, burn in oxygen atmosphere, make silicon and silicon oxide in the sample react to become silicon dioxide, carbon is burned and discharged as carbon dioxide, weigh and calculate silicon content ratio a1. Use 70% HCl and 50% HF solution with volume ratio 2:1, put negative electrode material into the solution and stir for more than 10 hours, wash and dry, and use the same method to measure the mass of the remaining material as m2, specific pore volume as p2, silicon content ratio a2, and the density of silicon material as 2.34. The deposition parameter γ of silicon material in negative electrode material is calculated by the following formula:

[0164]

[0165] 3. Specific surface area, total pore volume and porosity test of negative electrode materials and carbon matrix:

[0166] a) Taking silicon as the active material as an example, 150 mL of 20% HF acid solution by mass was dripped dropwise into 10 g of negative electrode material under stirring, which would generate SiF4 and H2 gas and release heat. After no gas was generated, the supernatant acid solution was removed by centrifugation, and 150 mL of 20% HF acid solution by mass was added to the negative electrode material again. After stirring for 12 hours, the supernatant acid solution was removed by centrifugation again, and then the negative electrode material was washed with pure water until it was neutral and dried to obtain the negative electrode material after the silicon material was removed, i.e., the carbon matrix;

[0167] b) The specific surface area of ​​the material was measured using the American Micromeritics TriStar 3000 specific surface area and pore size analyzer;

[0168] c) The pore volume of a material can be determined by gas adsorption measurements, while nitrogen adsorption is a technique that characterizes the porosity and pore size distribution of a material by condensing a gas in the pores of a solid. As the pressure increases, the gas first condenses in the pores with the smallest diameter, and the pressure increases until a saturation point is reached, at which all pores are filled with liquid. The nitrogen pressure is then gradually reduced to evaporate the liquid from the system. Analysis of the adsorption and desorption isotherms enables the determination of the pore volume and pore size distribution, as well as the contribution of the respective pore volumes of micropores, mesopores and macropores to the total pore volume.

[0169] 4. Powder conductivity test of negative electrode materials: The MCP-PD51 powder resistance test system of Mitsubishi Chemical of Japan was used to test the conductivity under the pressure point of 20KN, and the four-probe method was used to determine the volume resistivity of the sample. The instrument can measure the resistance of the powder, and then the computer automatically calculates the conductivity and resistivity of the powder.

[0170] 5. Gas production test of negative electrode materials:

[0171] a) placing 5 g of the negative electrode material in a sealed container, and adding deionized water until the remaining volume above the container is 60 mL;

[0172] b) sealing the container, mixing well, and storing at room temperature for one day;

[0173] c) After 24 hours, shake the container again to disperse the precipitate into the liquid.

[0174] Open the lid of the container, use a hydrogen detector to measure the concentration of hydrogen, and convert it to cc / (kg·day).

[0175] 6. Particle size test of negative electrode materials: D50 is measured using a laser particle size analyzer, and it has a symmetrical distribution similar to a normal distribution. In its volume reference distribution, the cumulative 50% diameter is D50, and so on, the cumulative 90% diameter is D90, and the cumulative 10% diameter is D10, so the particle size distribution of the material can also be obtained (D90-D10) / D50.

[0176] 7. Compacted density test of negative electrode materials: Using the American McNord CARVER 4350.22 powder compaction density meter, a sample of specified mass m is placed in a mold and a pressure of 1.0T is applied. After maintaining the pressure for 30S, the pressure is removed to test its thickness and the compacted density is calculated.

[0177] 8. Tap density test of negative electrode materials: Use the Quantachrome DAT-6-220 tap density tester to place a sample of specified mass in a measuring cylinder, vibrate it for a specified number of times (3000 times for routine testing), read the volume of the measuring cylinder after tapping and calculate the tap density.

[0178] 9. Carbon content test of negative electrode materials: Using the G4 ICARUS HF infrared carbon-sulfur analyzer from Bruker, Germany, the sample is burned in a high-temperature, oxygen-rich state, and the carbon element it contains is oxidized to carbon dioxide. The generated gas enters the infrared detector with the carrier gas, and the carbon content can be calculated by quantitatively analyzing the changes in the carbon dioxide signal.

[0179] 10. Electrochemical performance test:

[0180] The negative electrode materials prepared in the above embodiments and comparative examples were respectively mixed with sodium carboxymethyl cellulose, styrene-butadiene rubber, conductive graphite (KS-6) and carbon black (SP) in a ratio of 92:2:2:2:2 to prepare a slurry, uniformly coated on a copper foil and dried to prepare a negative electrode sheet, which was assembled into a button cell in an argon atmosphere glove box. The separator used was a polypropylene microporous membrane, the electrolyte used was 1 mol / L lithium hexafluorophosphate (the solvent was a mixed slurry of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate), and the counter electrode used was a metal lithium sheet.

[0181] The negative electrode materials prepared in the above examples and comparative examples were prepared into batteries, and the discharge specific capacity test was carried out on a Blue Power CT2001A battery test system. The ratio of the amount of electricity discharged in one hour to the battery capacity was the discharge specific capacity.

[0182] The negative electrode materials prepared in the above examples and comparative examples were prepared into batteries, and the first coulombic efficiency test was carried out on the Blue Power CT2001A battery test system, with a charge and discharge current of 0.05C, and the first coulombic efficiency was measured. The measured value is the average value of 3 to 5 button batteries of each material.

[0183] Please refer to Table 1 for some of the preparation conditions of the above Examples 1-14 and Comparative Examples 1-4, and please refer to Table 2 for the above test results.

[0184] Table 1. Partial preparation conditions of Examples 1-14 and Comparative Examples 1-4 of the present application

[0185] Reaction temperature (℃) Reaction pressure (kPa) Ammonia ratio (%) Reaction time (h) Example 1 800 100 10 2 Example 2 800 100 20 2 Example 3 600 100 10 2 Example 4 1000 100 10 2 Example 5 800 100 10 0.5 Example 6 800 100 10 4 Example 7 700 50 20 1 Example 8 800 50 50 0.5 Example 9 700 100 5 10 Example 10 800 100 10 2 Embodiment 11 800 / 10 2 Example 12 800 100 1 2 Embodiment 13 400 100 10 2 Embodiment 14 800 100 10 10min Comparative Example 1 / / / / Comparative Example 2 800 100 80 2 Comparative Example 3 1800 100 10 2 Comparative Example 4 800 100 10 20

[0186] Table 2. Performance test results of Examples 1-14 and Comparative Examples 1-4 of the present application

[0187]

[0188] Under the preparation process conditions of the present application, the negative electrode materials of Examples 1-14 contain nitrogen, and also form a structure in which a carbon matrix core with silicon material deposition and a core surface is coated with a coating layer, and the nitrogen element has a preset content and distribution trend in the negative electrode material, so that the pores of the carbon matrix have an enhanced adsorption capacity for the gas phase silicon source, which is conducive to improving the value of the deposition parameter γ to a certain extent, and is conducive to making the deposition parameter γ of the silicon material conform to the preset range, thereby relatively reducing the deposition of silicon material on the surface of the carbon matrix, reducing the side reaction between the surface of the negative electrode material and the electrolyte, and effectively reducing the gas production behavior of the negative electrode material. The above-mentioned negative electrode material has an excellent silicon material filling effect, a low gas production value, and the secondary battery using it has a correspondingly higher discharge specific capacity, first coulomb efficiency and better cycle stability.

[0189] Among them, Examples 1-9 and Examples 11-14 are also carbon-coated, so the comprehensive performance of the obtained negative electrode material is better. Examples 1-11 and 13 further meet the preset ranges of α and β, so the comprehensive performance of the obtained negative electrode material is better. In the carbon matrix nitrogen doping process of Examples 1 and 2, Examples 3 and 4, and Examples 5 and 6, the amount of ammonia, the reaction temperature and the reaction time are increased successively within the appropriate range, and the values ​​of α and β in the obtained negative electrode material are increased accordingly and α<β is maintained.

[0190] Compared with Example 1, Comparative Example 1 does not perform nitrogen doping treatment on the carbon matrix, and the detected amount of nitrogen atoms in the negative electrode material is low, which can be regarded as the background value of the nitrogen element in the negative electrode material. The nitrogen element is evenly distributed in the negative electrode material, so α and β are basically equal. However, relying on the adsorption capacity of the carbon matrix of Comparative Example 1 itself for the gas-phase silicon source, the silicon material filling effect of the obtained negative electrode material is not ideal (γ is smaller than that of Example 1), and the proportion of silicon material distributed on the surface of the carbon matrix is ​​relatively large, and the gas production behavior is more intense, which affects the conductive performance of the carbon matrix and also leads to an increase in the specific surface area of ​​the negative electrode material, thereby resulting in the discharge specific capacity and the first coulombic efficiency of the obtained secondary battery being inferior to those of Example 1.

[0191] Compared with Example 1, in the process of nitrogen doping the carbon matrix in Comparative Example 2, excessive ammonia is used, resulting in excessive nitrogen doping in the carbon matrix, which is not conducive to controlling the relationship between α and β, resulting in α>β. In the process of nitrogen doping the carbon matrix in Comparative Example 3, too high a temperature is used, which may lead to a faster cracking rate of ammonia, chaotic attachment of nitrogen atoms, and may also cause the collapse of the carbon matrix structure, which is not conducive to controlling the relationship between α and β, resulting in α>β. At the same time, too high a temperature also aggravates the degree of graphitization of the carbon matrix, which is not conducive to the deposition of silicon materials. In the process of nitrogen doping the carbon matrix in Comparative Example 4, too long a reaction time is used, which may cause the subsequent cracked nitrogen to be easily doped in the more superficial area of ​​the carbon matrix, resulting in α>β. The proportion of silicon materials distributed on the surface of the carbon matrix in the above negative electrode materials is also relatively large, and the gas production behavior is violent, which affects the performance of the conductive properties of the carbon matrix, and also leads to an increase in the specific surface area of ​​the negative electrode material, thereby limiting the discharge capacity and first coulomb efficiency of the obtained secondary battery.

[0192] In summary, the present application provides an improved method for preparing negative electrode materials. Under the process conditions of the preparation method, the obtained negative electrode material has α, β and γ that meet the preset range, and α and β meet the preset relationship, so that the distribution of active substances in the obtained negative electrode material on the carbon matrix has an excellent filling effect, reduces the gas production behavior of the negative electrode material and is beneficial to the conductivity of the carbon matrix, so that the secondary battery using the negative electrode material has a higher discharge specific capacity, first coulomb efficiency and better cycle stability.

[0193] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material contains nitrogen, and the negative electrode material includes a carbon matrix and an active substance, the carbon matrix is ​​provided with pores, and at least part of the active substance is provided in the pores of the carbon matrix, a region with a depth of 200 nm from the outer surface of the negative electrode material is defined as a first region, and a region with a depth of 1000 nm from the outer surface of the negative electrode material is defined as a second region, the atomic percentage content of the nitrogen element in the first region is α, and the atomic percentage content of the nitrogen element in the second region is β, α<β; Define the deposition parameter of the active material as γ, Wherein, ρ is the density of the active substance; m1 is the mass of the negative electrode material. Based on m1, the mass percentage of the active material is a1, and the specific pore volume of the negative electrode material is p1; m2 is the mass of the negative electrode material after removing the active substance. Based on m2, the mass percentage of the active substance is a2, and the specific pore volume of the negative electrode material after removing the active substance is p2.

2. The negative electrode material according to claim 1, characterized in that 0.5≤α<β≤10。 3. The negative electrode material according to claim 1, characterized in that The negative electrode material comprises a core and a coating layer provided on at least a portion of the surface of the core, the core comprises the carbon matrix and an active material, and the coating layer satisfies at least one of the following conditions: (1) The material of the coating layer includes one or more of carbon materials, metal oxides, amorphous silicon, conductive polymers, fluorides, phosphates and nitrides; (2) The coating layer has a thickness of 5 nm to 200 nm; (3) The mass proportion of the coating layer in the negative electrode material is less than or equal to 10%.

4. The negative electrode material according to claim 1, characterized in that The carbon matrix satisfies at least one of the following conditions: (1) The specific surface area of ​​the carbon matrix is ​​800 m 2 / g to 3000m 2 / g; (2) The total pore volume of the carbon matrix is ​​0.5 cm 3 / g to 2.0cm 3 / g; (3) The porosity of the carbon matrix is ​​40% to 80%; (4) The carbon matrix includes one or more of hard carbon, soft carbon, natural graphite, artificial graphite, carbon nanotubes, carbon fibers and graphene.

5. The negative electrode material according to claim 1, characterized in that The active substance meets at least one of the following conditions: (1) The active material includes one or more of Li, Na, K, Sn, Ge, Si, Fe, Mg, SiO, Ti, Zn, Al, P and Cu; (2) The active material includes a silicon material, and the silicon material includes one or more of amorphous silicon, crystalline silicon, and a composite of crystalline silicon and amorphous silicon; (3) The active material includes silicon material, and the silicon material includes one or more of silicon particles, silicon oxide, and silicon alloy; (4) The active material includes a silicon material, the silicon material includes silicon particles and a silicon oxide layer located on the surface of the silicon particles, and the silicon oxide layer includes silicon oxide; (5) The active material includes silicon material, and the average particle size of the silicon material is 0.1 nm to 500 nm.

6. The negative electrode material according to claim 3, characterized in that The active material includes a silicon material, the coating layer includes a carbon material, and the negative electrode material satisfies at least one of the following conditions: (1) Based on the mass of the negative electrode material, the mass proportion of carbon element in the negative electrode material is 40% to 60%; (2) Based on the mass of the negative electrode material, the mass proportion of silicon element in the negative electrode material is 30% to 65%.

7. The negative electrode material according to claim 1, characterized in that The negative electrode material also satisfies at least one of the following conditions: (1) The specific surface area of ​​the negative electrode material is 0.5 m 2 / g to 10m 2 / g; (2) The powder conductivity of the negative electrode material is 0.5S / cm to 3S / cm; (3) The 24-hour gas generation value of the negative electrode material is less than or equal to 4cc / kg.

8. The negative electrode material according to claim 1, characterized in that The negative electrode material also satisfies at least one of the following conditions: (1) The median particle size of the negative electrode material is 5 μm to 20 μm; (2) The particle size distribution (D90-D10) / D50 of the negative electrode material is 0.9 to 5; (3) The compaction density of the negative electrode material under a pressure of 1T is 0.8 g / cm 3 Up to 1.3g / cm 3 ; (4) The tap density of the negative electrode material after 3000 vibrations is 0.5 g / cm 3 Up to 1.5g / cm 3 .

9. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, characterized in that: The negative electrode active material layer comprises the negative electrode material according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Nitrogen-doped porous silicon carbon negative electrode material and preparation method and application thereof

    CN119038558A

  • Negative electrode material and preparation method therefor, electrochemical device, and electronic device

    WO2022193123A1

Cited By

  • Negative electrode material, negative electrode sheet and secondary battery

    WO2025201570A1

  • Negative electrode material, negative electrode sheet, and secondary battery

    WO2026148922A1